Psychological analysis of the characteristics of self-conscious future psychologists in the educational and professional activities - M. Grintsіv (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This paper analyzes the features of conscious self-regulation in the process of teaching and professional activities. And the most important functional link structure of conscious self-regulation, as well as basic factors and conditions of conscious self-regulation and their role in the optimization of teaching process in educational institutions. The results of an empirical study of the stylistic features of self-regulation of psychology students as part samorehulyatyvnoho process.